فاعلية السياسة المالية ودورها في تحقيق التوازن الاقتصادي دراسة حالة الاقتصاد الليبي خلال الفترة 2012 -2023 - موسى, عزالدين عبد السلام الكيلاني (Sharwes Scientific Journal, 2024)
The study aims to find out the effectiveness of fiscal policy in achieving economic balance through an analytical study of the state of the Libyan economy for the period 2012-2023. To achieve the objective of the study, the concept of fiscal policy and its most important objectives were reviewed, the development of economic thought in addition to the concept of economic balance, and the analysis of the reality of fiscal policy in the Libyan economy during the period 2012-2023 through the development of public revenues and public expenditures and analysis of internal balance through the general budget and external balance through the trade balance, and the study concluded that the mechanisms of fiscal policy were not effective enough in achieving economic balance